2020
DOI: 10.1016/j.mehy.2020.110180
|View full text |Cite
|
Sign up to set email alerts
|

The AI-discovered aetiology of COVID-19 and rationale of the irinotecan+ etoposide combination therapy for critically ill COVID-19 patients

Abstract: We present the AI-discovered aetiology of COVID-19, based on a precise disease model of COVID-19 built under five weeks that best matches the epidemiological characteristics, transmission dynamics, clinical features, and biological properties of COVID-19 and consistently explains the rapidly expanding COVID-19 literature. We present that SARS-CoV-2 implements a unique unbiased survival strategy of balancing viral replication with viral spread by increasing its dependence on (i) ACE2-expressing cells for viral … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…14 Second, it has been shown to suppress RNA virus replication in in vitro studies. 15 The combination of etoposide and dexamethasone also has been shown to be successful in the treatment of hyperinflammatory syndromes associated with other viral illnesses such as severe swine flu A/H1N1, and avian influenza A/H5N1 infections. 16,17 In addition, our modified dose of 50 mg/m 2 was based on aforementioned Swine influenza A/H1N1-related hyperinflammatory syndromes in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…14 Second, it has been shown to suppress RNA virus replication in in vitro studies. 15 The combination of etoposide and dexamethasone also has been shown to be successful in the treatment of hyperinflammatory syndromes associated with other viral illnesses such as severe swine flu A/H1N1, and avian influenza A/H5N1 infections. 16,17 In addition, our modified dose of 50 mg/m 2 was based on aforementioned Swine influenza A/H1N1-related hyperinflammatory syndromes in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…In animal experiments, estrogen therapy suppressed inflammatory reactions and cured COVID-19 infection (54).Based on the results of this study, olaparib and irinotecan had a suitable free binding energy with CD147 ( Table 3 ). A relevant study demonstrated that a combination of irinotecan (topoisomerase I inhibitor) and etoposide (a topoisomerase II inhibitor) can potentially inhibit cytokine storms in COVID-19 ( 55 ). A type of clinical study using a drug repositioning strategy indicated the inhibitory effects of olaparib and mefuparib, as two PARP1 inhibitors, on COVID-19 ( 56 ).…”
Section: - Discussionmentioning
confidence: 99%
“…Our combined machine learning and docking strategy return high binding affinity ligands consistent with previous computational screens of the ACE2 receptor. Furthermore, sorafinib, [ 42 ] irinotecan, [ 43 ] and nilotinib [ 44 ] ( Table S1 ) show reduction in infection rates in cell assays studies, while zanubrutinib is currently in clinical trial. Although these drugs target other pathways involved in the pathology, the reduction in infection rate could be in part attributed to the ability of the drug to bind ACE2.…”
Section: Resultsmentioning
confidence: 99%